2011
DOI: 10.1371/journal.pone.0023776
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Mitochondrial Uncoupling Protein Confers Tolerance to Drought and Salt Stress in Transgenic Tobacco Plants

Abstract: BackgroundPlants are challenged by a large number of environmental stresses that reduce productivity and even cause death. Both chloroplasts and mitochondria produce reactive oxygen species under normal conditions; however, stress causes an imbalance in these species that leads to deviations from normal cellular conditions and a variety of toxic effects. Mitochondria have uncoupling proteins (UCPs) that uncouple electron transport from ATP synthesis. There is evidence that UCPs play a role in alleviating stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 60 publications
5
71
0
4
Order By: Relevance
“…In addition to the previous observation of increased tolerance to oxidative, salt, and drought stresses [11,12], we observed that the P07 UCP1 overexpressor performed better under low and high pH, hyperosmotic stress, and oxidative stress (Figure 6A). Additionally, in the presence of free fatty acids, the P07 transgenic line also exhibited improved performance under low temperature, a result that support the thermogenic role of plant UCP1 (Figure 6A).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In addition to the previous observation of increased tolerance to oxidative, salt, and drought stresses [11,12], we observed that the P07 UCP1 overexpressor performed better under low and high pH, hyperosmotic stress, and oxidative stress (Figure 6A). Additionally, in the presence of free fatty acids, the P07 transgenic line also exhibited improved performance under low temperature, a result that support the thermogenic role of plant UCP1 (Figure 6A).…”
Section: Resultssupporting
confidence: 82%
“…Although UCP1 acts directly in the mitochondrial respiratory chain by uncoupling the electron transport from ATP synthesis, no apparent phenotypic alterations were observed in the P49 and P07 transgenic lines compared with the wild-type (WT) plants (Figure 1A). This result diverges from previous findings showing increased shoot dry mass in plants overexpressing the same UCP1 [12], but it is consistent with observations of tomato plants overexpressing a UCP, which did not exhibit growth stimulation [13]. The addition of sucrose to the growth medium may have altered mitochondrial metabolism and biogenesis [24].…”
Section: Resultssupporting
confidence: 80%
“…Due to the complexity of functional genes in response to salt stress, conventional breeding program is relatively hard to be executed effectively (Flowers 2004;Shabala and Cuin 2008;Shao et al 2009Shao et al , 2010. Although many studies have announced that salt tolerance was enhanced in transgenic plants (Begcy et al 2011;Hao et al 2011;Jacobs et al 2011;Rahnama et al 2011;Wei et al 2011), the results are obtained under abnormal growth condition and not tested in the field. Stress resistance training and exogenous application of growth and osmotic regulators have been demonstrated to ameliorate plant salt stress (Amzallag et al 1990;Umezawa et al 2000;Chattopadhayay et al 2002;Demiral and Turkan 2006;Chen et al 2007;Kaya et al 2007;Wahid et al 2007;Athar et al 2008;Zheng et al 2008;Reezi et al 2009;Chang et al 2010;Cimrin et al 2010;Khan et al 2010;Akram and Ashraf 2011;Fan et al 2011;Idrees et al 2011;Lin et al 2011;Nazar et al 2011;Sakr et al 2012).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Cellular respiration is one of the common phenomena enhanced in both plants (Livne and Levin 1967;Begcy et al 2011) and cyanobacteria (Molitor et al 1990;Rai et al 2014;Jeanjean et al 1993;Srivastava et al 2008) when exposed to salt stress. There is a line of evidence supporting the above fact, and this has been linked in some way with higher energy requirement of salt-affected cells in order to maintain turgor, ion homeostasis and production of more osmolytes.…”
Section: Cellular Metabolismmentioning
confidence: 99%